2014
DOI: 10.1111/vru.12177
|View full text |Cite
|
Sign up to set email alerts
|

Contrast‐enhanced Ultrasonographic Findings in Three Dogs With Pancreatic Insulinoma

Abstract: Abdominal ultrasonography is one of the most common diagnostic imaging modalities used for dogs with suspected insulinoma; however, pancreatic masses are clearly identified in fewer than half of affected dogs and benign pancreatic nodules can be difficult to differentiate from malignant ones. The purpose of this prospective study was to describe contrast-enhanced ultrasonography (CEUS) characteristics of confirmed pancreatic insulinoma in a group of dogs. Inclusion criteria were as follows: (1) repeated hypogl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
24
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 32 publications
4
24
1
Order By: Relevance
“…Previous canine studies have shown an increased number of nodules in the pancreas and improved anatomic localization with CEUS (contrast-enhanced ultrasound) compared with conventional ultrasound [4]. In addition, the nodule margins have been better demarcated with CEUS [4] [6]. However, in a recent case series of three dogs with pancreatic nodules with histologically confirmed insulinoma the nodules were visible using both conventional and CEUS [6].…”
Section: Introductionmentioning
confidence: 99%
“…Previous canine studies have shown an increased number of nodules in the pancreas and improved anatomic localization with CEUS (contrast-enhanced ultrasound) compared with conventional ultrasound [4]. In addition, the nodule margins have been better demarcated with CEUS [4] [6]. However, in a recent case series of three dogs with pancreatic nodules with histologically confirmed insulinoma the nodules were visible using both conventional and CEUS [6].…”
Section: Introductionmentioning
confidence: 99%
“…A study in dogs on contrast‐enhanced ultrasound demonstrated a difference in enhancement patterns of insulinomas and pancreatic adenocarcinomas . Meanwhile, another study on contrast‐enhanced ultrasound suggested that this modality may help to increase the conspicuity of canine insulinomas; however, enhancement characteristics in the examined patients were variable . Computed tomography, including dynamic CT, dual‐phase CT angiography, and triple‐phase CT, has appeared promising for identification of pancreatic insulinomas and their metastases in both canines and humans, but the enhancement pattern of canine insulinomas on CT remains to some extent inconsistent .…”
Section: Introductionmentioning
confidence: 99%
“…In 4 dogs, nonenhancing pancreatic parenchymal lesions were identified on CEUS. The enhancement characteristics of these lesions (nonenhancement) on CEUS suggest areas of pancreatic ischemia or necrosis instead of neoplasia such as pancreatic insulinoma (hypo‐enhancement or hyper‐enhancement) or adenocarcinoma (hypo‐enhancement) . However, histopathologic confirmation was not available in this study.…”
Section: Discussionmentioning
confidence: 73%
“…Perfusion of various abdominal organs such as the liver, spleen, pancreas, kidney, and adrenal glands can be studied noninvasively using CEUS . Applications of CEUS in the diagnosis of pancreatic neoplasia also have been reported in veterinary medicine . CEUS utilizes microbubble (MB) contrast agents that remain entirely intravascular when administered IV, with no extravasation into surrounding tissue .…”
mentioning
confidence: 99%